PERLINDUNGAN SAKSI DAN KORBAN DALAM PROSES PENEGAKAN HUKUM PIDANA - Yudi Krismen (UIR PRESS, 2016)
Speaking about victims and witnesses, we can not be separated rather than criminal proceedings. In the provision of Article 184 paragraph (1) letter a witnesses KUHAP positioned as